Urinary parabens in children from South China: Implications for human exposure and health risks. (November 2019) - Lu, Shaoyou; Ren, Lu; Liu, Yanlin; Ma, Huimin; Liu, Shan; Zhu, Zhou; Tang, Zhi; Kang, Li; Liao, Shicheng
Abstract: Parabens are extensively applied in cosmetics, drugs or food as preservatives and have become common pollutants in environmental media. However, data on human exposure to these chemicals is still limited, especially for children. This study aimed to investigate parabens in urine samples of children and to evaluate the cumulative risk of paraben exposure. Five short-chain parabens were measured in 255 urine samples collected from children in a kindergarten and elementary schools from South China. Methyl paraben (MeP), ethyl paraben (EtP) and n-propyl paraben (PrP) were widely detected in urine samples (detection rates > 94.9%), indicating their widespread exposure. The urinary median concentrations of MeP, EtP and PrP were 2.25, 0.33 and 0.50 μg/L, respectively. Significantly positive correlations ( p  < 0.01) were observed between MeP and PrP in urine, suggesting similar sources and/or metabolic pathways of these two chemicals. The median estimated daily intakes (EDIs) of parabens were determined to be 18.1 and 9.79 μg/kg-bw/day for kindergarten children and elementary school students, respectively. Estimation of human intake and exposure risks indicated potential risks of PrP exposure for elementary school students. This is the first study addressing paraben exposure in South China children. Graphical abstract: Image 1 Highlights: Children in South China are widespread exposed to parabens. Significantly positive associations were observed between urinary methyl and n-propyl parabens. Elementary school students were subjected to potential risks of n-propyl paraben exposure. Abstract : Estimation of human intake and exposure risks indicated potential risks of n -propyl paraben exposure for elementary school students in South China.